Productivity of Vegetable Hummingbird Tree Legumes Seeds or White Turi (Sesbania grandiflora L.) by Soaking in Rice Washing Water and Coconut Water - Wahyudi Himawan Sutanto; Rizka Ramadhani; Bayriel Dudeq Opok (Talenta Publisher, 2025)
Rice washing water and old coconut water are commonly regarded as household waste, despite their potential as sources of nutrients and natural plant growth regulators. This study aimed to evaluate the effect of soaking white turi legume seeds (Sesbania grandiflora L.) in rice washing water and old coconut water at different concentrations on seed productivity. The research was conducted in Medan City from February to March 2025 using a Completely Randomized Design (CRD) with five treatments and four replications, namely: control (distilled water), 100% rice washing water, 100% old coconut water, a combination of 20% old coconut water + 80% rice washing water, and a combination of 50% old coconut water + 50% rice washing water. Observed parameters included growth potential, vigor index, plumule length, radicle length, and number of radicle branches. Data were analyzed using analysis of variance (ANOVA) followed by Duncan’s Multiple Range Test (DMRT) at a 5% significance level. The results showed that soaking seeds in 100% rice washing water and in the combination of 20% old coconut water + 80% rice washing water produced the highest growth potential and vigor index (90%). In contrast, 100% old coconut water resulted in the lowest performance for most parameters, particularly vigor index and radicle length. The greatest plumule length was numerically observed in the 100% rice washing water treatment, while the number of radicle branches did not differ significantly among treatments. In conclusion, rice washing water, either applied alone or combined with low concentrations of old coconut water, can enhance seed productivity and vigor of white turi, indicating its potential use as a natural and environmentally friendly plant growth regulator.